Nuclear radii of excited states in A=17 isoquartets - Nakamura, S.; Guimaraes, V; Kubono, S. (Elsevier B.V., 1998)
The Coulomb energy is evaluated by a harmonic oscillator wave function. It explains the experimental parity-dependence of the Coulomb mass shifts of A = 17 isoquartets, suggesting a level-dependent nuclear radius. It also suggests that the two protons of the ground state of Ne-17 occupy the 1s1/2(+)-orbit. (C) 1998 Published by Elsevier Science B.V.